The development of teachers in the middle school, a case study (Praxis Educativa, 2012)
The work presents the conclusions of a research carried out with middle school teachers from Córdoba City, at the end of 2002. It focused on the professional development of the teachers in work areas under different working situations. In the presentation, contextualized aspects of the problem-situation are considered as well as a brief background account of prestudies and concepts that led up to and empirical work. It also makes reference to the theoretical-methodological focus of the research in which it is explained that one case study is chosen and the teacher's narrations are privileged Finally, a great deal of importance is given to the most relevant conclusions of the research in relation to the topic and the problem situation presented.
Keywords: training; development; middle school teachers; biographies; narrations